Validation of technological process of preparation hymoding cream with hyaluronic acid - T. G. Yarnykh; G. M. Melnik; O. A. Rukhmakova (The State Expert Center of the Ministry of Health of Ukraine, 2021)
To date, in the mass production of medicines both in pharmaceutical companies and in pharmacies, more and more attention is paid to the practice of process validation. Validation is a key condition for the implementation of Good Manufacturing (GMP) and Pharmacy (GPP) practices, the standards of which are mandatory for medicines worldwide and in Ukraine. The aim of the work - validation of the technological process of preparation extemporaneous hymoding cream with hyaluronic acid in order to obtain documentary evidence of effective reproduction of the preparation of this medicine. The study design is based on research on the development of dosage form technology, analysis of the impact of critical manufacturing points and evaluation of their impact on the final quality of the cream, taking into account the requirements of GPP. The object of validation is the technological process of preparation hymoding cream with hyaluronic acid. The validation procedure was performed on 3 experimental batches of the medicine. In order to check and optimize the selected technological process of preparation hymoding cream in pharmacies, its validation was carried out. According to the calculated quantities of the components of the studied cream, as well as the identified critical parameters, three batches of the medicine of 100.00 g were developed. On the series of cream, the optimization of technological parameters, testing of critical parameters for all planned stages of production with the definition of eligibility criteria and validation scheme was carried out. Acceptance criteria for all critical parameters were determined during the optimization of technology on batches of the studied medicine. The general risk assessment was carried out at the stage of pharmaceutical development according to the procedure «identification - analysis - risk assessment» to determine the scheme of validation work on batches of the medicine. During the technological process, critical indicators were checked and appropriate forms were filled out. A study on the validation of the technological process of preparation hymoding cream with hyaluronic acid in pharmacies was performed. Documentary evidence of effective reproduction of the manufacture of this medicine has been obtained. A comprehensive analysis of the developed manufacturing process makes it possible to identify critical control points that minimize the occurrence of possible risks in the manufacture of the investigated medicine. According to the results of the research, it can be concluded that the developed cream with hyaluronic acid meets the requirements of State Pharmacopoeia of Ukraine in all quality indicators, which allows to recommend it for use in dermatology.